An Exploration Into the Human Resource Management in Public Health Services Of Kerala - Praveenlal Kuttichira; Sreekumari AND Rajamohanan (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH, 2016)
The paradox of High morbidity- low mortality in Kerala is a widely discussed observation. One reason for that could be the efficiency of care which cure the disease before progressing to death, which in turn depends on the efficiency of the treating team. This study attempted to examine some of the key aspects related to Human Resource management in the Public Health services. Published official reports were searched and data gathered related to availability of institutions and manpower in public health care in Kerala. The data was analysed against the actual requirements. Though actual availability of institutions Kerala state is more than the national standards, there is non-availability of trained staff. There is no paucity of doctors, but it is the paucity of specialists. There do exist scarcity for nurses while the seats in nursing colleges remain vacant. Growth of health care in the private sector surpassed that in the public sector recently. Small or medium hospitals in the state are getting closed down. Charity hospitals also show same trend. Practices existing in private hospitals were reported to be not conducive for deliver- ing quality healthcare to the stake holders. Decentralised planning failed to improve human resource management. The Cooperative sector have potential in addressing many issues in the field of heath care. But it is yet to prove its effect. Kerala also face increasing feminisation of Medical Profession and resulting issues. Planned correction of mismatches with in the available institutions, categories of manpower and training facilities are suggested. The need to base it on a robust health policy is highlighted. Strengthening of Co-operative sector, supports for small and medium hospitals and rethinking in workforce planning to ensure gender justice are suggested